Gender-based Interpersonal Communication Behavior: When Women No Longer Muted - Happy Wulandari; Dyah Pithaloka; Sherly Aidya Pasya (LONTAR: Jurnal Ilmu Komunikasi, 2025)
This is a study using interview methods, focus group discussions, and systematic literature reviews. The problem is positioned on the change in the form of communication between women in the past and present. In an environment that supports the form of communication in the passive category, contemporary women today are gradually using the assertive category, especially in the context of romantic interpersonal relationships. Previously, in this category, women were expected to behave passively. In the explanation, muted group theory, patriarchal culture, and emotional intelligence of women will also be touched on to better understand the change in the form of communication in contemporary conditions.